Isolasi Kitin Dari Limbah Cangkang Kepiting Bakau (Scylla Olivacea) Dengan Variasi Konsentrasi Natrium Hidroksida Dan Suhu Pada Proses Pembuatan Serbuk Kitin - Darmiyati, Siti; Drastinawati, Drastinawati; Yusnimar, Yusnimar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Chitin is poly (2-acetamido-2-deoxy-β(1,4)-D-glucopyranose). Chitin can be isolated through several stages of chitin powder production, demineralization stage and bleaching stage. The purpose of this study is to learn the effect of concentration of sodium hydroxide and temperature in the process of chitin powder production, analyze chitin by using FTIR (Fourier Transform Infrared) spectrophotometer and determining moisture content, ash content and yield. The research procedure begins with crab shell waste size reduction into a powder size. The process of chitin powder production was carried out using concentration of NaOH variations (2.5%, 3.5% and 4.5%) and temperature (550C, 650C dan 750C), the ratio of 1:10 (w/v) for 2 hours and stirring speed 150 rpm, then demineralization process using HCl 1.5 N, the ratio of 1:15 (w/v) for 1 hour and stirring speed 150 rpm, then bleaching process using 4% NaOCl, the ratio of 1:15 (w/v) for 1 hour. The results showed that the higher concentration of NaOH and temperature, the yield, the water content and the resulting ash content were lower at 4.5% NaOH concentration and 750C at 15.54%, 4.13% and 0.5%. Based on the results of the obtained FTIR showed that the residue from isolation was chitin.Keywords: bleaching, crab shells, demineralization, FTIR, chitin.